Model-reference control of chaotic systems - Ucar, Ahmet (Pergamon-Elsevier Science Ltd, 2007)
In this paper, the problem of controlling chaotic systems is studied. A control law is introduced for a chaotic system to follow a desired reference system. The control strategy is developed within the general framework of the nonlinear model-reference control systems. Lyapunov stability is used to ensure the global stability of the error dynamics represents the difference between the desired and chaotic systems. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Nonfeedback Methods